Comparative Study Of Leadership Style, Workload And Motivation Of Nurses To Improve The Quality Of Services At Health Service Unit - Sureskiarti, Enok; Zulaikha, Fatma; Murnisiah, Ery; Vera, Lidya; Sanjaya, Raenaldy (Akademi Kebidanan Bunga Husada Samarinda, 2020)
Background: Puskesmas as a first level health service center is required to provide quality, fair and affordable health services. The aim of improving quality health services is to form good relationships with patients so that patients remain loyal to the Puskesmas1. Nurses are one of the largest health service teams who are required to improve the quality of service in the health service unit. One of the factors that influence the service quality of nurses is internal factors, namely motivation. The higher a person's motivation, the stronger the impetus for working harder so that it can improve the quality of service. In addition to internal factors, nurse performance is also influenced by external factors, including the workload factor of nurses and the leadership of the organizational unit. The purpose of this study was to conduct a comparative study of the effect of the three mentioned factors on the quality of health services at Long Ikis Public Health Center in Paser Regency, East Kalimantan. This study is a descriptive correlation study with a cross-sectional approach. The number of samples in this study were 35 nurses who worked at the Long Ikis Community Health Center with a distribution of 19 nurses at the main health center and 16 nurses in 14 sub-health centers in Paser district. The bivariate test used for nurses' motivation and workload used the chi-qure test with the following results for workload P = 0.458. Which means there is no relationship between workload and quality of nursing services, for the Motivation Factor the result is p = 0.032, which means p kurang dari α (0.05) and it can be concluded that there is a relationship between nurses' motivation and the quality of health services at Long Ikis Public Health Center. Whereas for the leadership factor tested with lineer regression with the results of the Transformational Leadership Style not significantly related to the Quality of Health Services at Long Ikis Health Center with tcount kurang dari ttable (-1.273 kurang dari 2.025) at 5% significance and correlation coefficient (r) 0.216; (3) Transactional Leadership Style has no significant relationship with the Quality of Health Services at Long Ikis Health Center with tcount kurang dari ttable (0.803 kurang dari 2.025) at 5% significance and correlation coefficient (r) 0.238. The conclusion of this study is that there is a relationship between the motivation of nurses on the quality of service and there is no significant relationship between the workload of nurses and leadership styles on the quality of service at Long Ikis Public Health Center, East Kalimantan.